Management of Organic and Non-Organic Waste in Tunjungmuli Village, Karangmoncol District - Adelia Putri Maharani Mursidah; Putri Olivia Nurman; Rizki Widodo; Selfianatun Nisa; Riko Abim Saputro; Rifky Alifudin; Dika Abdan Wibowo; Edo Aji Saputro; Ayu Sitanini (Dimas Canthing : Jurnal Pengabdian Masyarakat, 2026)
This study discusses the management of organic and non-organic waste in Tunjungmuli Village, Karangmoncol District, Purbalingga Regency. The community service program implemented included socialization, guidance, training on the use of plastic waste to make handicraft products, and the processing of organic waste into compost. The results of the activities showed an increase in the awareness and understanding of the community and students regarding the importance of proper and sustainable waste management by applying the 3R (Reduce, Reuse, Recycle) principle. Organic waste was successfully processed into compost that is useful for agriculture, while inorganic waste was utilized into products with economic value such as recycled bags and wallets. This program also instilled environmental awareness in the younger generation. In conclusion, waste management in Tunjungmuli Village has succeeded in improving the community's skills and creativity in managing waste effectively and independently, and has the potential to become a model for community-based waste management that can be applied in other areas.   [1][2][3] Desa, D., & Bondowoso, P. (2021). Edukasi Pengelolaan Dan Pemilahan Sampah Organik Dan Anorganik. 1(1), 61–69. [4] Sekarningrum B, Sugandi Y, Yunita DKumawula: Jurnal Pengabdian Kepada Masyarakat, Sosialisasi dan Edukasi Kangpisman (Kurangi, Pisahkan dan Manfaatkan Sampah) (2020) 3(1) 73 [6] Widiyono A, Fitriyana S, Nihaya KJournal Of Human And Education (JAHE)(2022)2(2) 8-12 [5] Jurnal A, Lova Sari G, Kajian Potensi Pemanfaatan Sampah Plastik Menjadi Bahan Bakar Cair (2017) 3(1) 6-13 [7] Diana S, Amalia Z, Kegiatan Pelatihan Pemanfaatan Sampah Plastik Menjadi Produk Kerajinan Tangan Bernilai Ekonomis A(2017) 2548 4117